1993
DOI: 10.1007/bf03009627
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of epidural tramadol and epidural morphine for postoperative analgesia

Abstract: Epidural morphine has been used for postoperative analgesia. However, many side effects such as nausea, vomiting, pruritus, urinary retention, and delayed respiratory depression have been reported. 1-6 Although rare, delayed resporatory depression is the most serious complication and may occur several hours after the administration of epidural morphine.One(m-methylphenyl)-2-(dimethylaminoethyl)-cyclohexan-l-01(tramadol; Tramal*) 7 is a new synthetic opioid CAN J ANAESTH 1993 / 40:4 / pp 308-13

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
72
0
7

Year Published

1993
1993
2012
2012

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 100 publications
(85 citation statements)
references
References 24 publications
6
72
0
7
Order By: Relevance
“…Baraka et al 21 reported that epidural tramadol (100 mg) provided adequate and prolonged postoperative analgesia similar to that produced by epidural morphine (4 mg) in patients undergoing major abdominal surgery without respiratory depression. In contrast, the mean PaO 2 in patients who received epidural morphine was decreased from the sixth hour postoperatively.…”
Section: Part 2: Postoperative Analgesiamentioning
confidence: 97%
See 1 more Smart Citation
“…Baraka et al 21 reported that epidural tramadol (100 mg) provided adequate and prolonged postoperative analgesia similar to that produced by epidural morphine (4 mg) in patients undergoing major abdominal surgery without respiratory depression. In contrast, the mean PaO 2 in patients who received epidural morphine was decreased from the sixth hour postoperatively.…”
Section: Part 2: Postoperative Analgesiamentioning
confidence: 97%
“…In contrast, the mean PaO 2 in patients who received epidural morphine was decreased from the sixth hour postoperatively. 21 Previous clinical reports have also shown that parenteral morphine resulted in greater, and clinically important, respiratory depression than equi-analgesic doses of parenteral tramadol. 3, 22 Naguib et al 23 reported that the incidence of postoperative nausea and vomiting (PONV) after laparoscopic cholecystectomy was 72.4% which was reduced to 34.5% after prophylactic administration of 4 mg ondansetron.…”
Section: Part 2: Postoperative Analgesiamentioning
confidence: 98%
“…Tramadol may be advantageous because of a low risk of respiratory depression. 2,3 Tramadol is a weak agonist at all types of opioid receptors with some selectivity for µ receptors. Also, tramadol inhibits the reuptake of norepinephrine and serotonin, thus increasing the concentrations of these two neurotransmitters in the central nervous system.…”
mentioning
confidence: 99%
“…The relatively low lipid solubility of morphine is thought to account for its tendency for cephalad spread in the CSF. Thus, close observation is recommended for 24 hr after the last injection) [6][7][8][9][10][11][12][13][14][15][16][17][18][19] Tramadol is a weak agonist at all types of opioid receptors with some selectivity for p receptors} ~ Also, mechanisms of action ofnon-opioid receptors may contribute to the analgesic profile. Tramadol inhibits noradrenaline uptake and stimulates serotonin release, and these are transmitters in the descending inhibitory pathways which enhance analgesia.…”
Section: Discussionmentioning
confidence: 99%